Meningkatkan nilai perusahaan: peran strategis kepemilikan institusional, leverage keuangan dan kebijakan dividen di perusahaan Indonesia - Sunjaya, Robi; Bertuah, Eka (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study evaluates the impact of institutional ownership and financial leverage on firm value, with dividend policy serving as a mediating variable. The primary focus is to examine how dividend policy mediates the relationship between institutional ownership and firm value, as well as the effect of financial leverage on firm value. By using panel data regression models, the research incorporates purposive sampling, selecting 125 companies from a population of 902 firms listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023, resulting in a total of 500 observations. The findings reveal that institutional ownership has a significant and positive impact on firm value, while financial leverage does not have a notable effect. Additionally, while dividend policy positively influences firm value, it does not mediate the relationship between institutional ownership and firm value. However, dividend policy successfully mediates the effect of financial leverage on firm value. These results highlight the critical role of institutional ownership and effective dividend policies in enhancing firm value. Practically, the study underscores the importance of institutional investors' oversight and the need for transparent dividend policies. For managers, ensuring effective dividend distribution can serve as a signal to the market, while policymakers should consider strengthening regulatory frameworks to support transparency. The study contributes to the academic literature by providing insights into the dynamics of the Indonesian market.